Time to Recovery from Severe Acute Malnutrition and Its Predictors among Admitted Children Aged 6-59 Months at the Therapeutic Feeding Center of Pawi General Hospital, Northwest Ethiopia: A Retrospective Follow-Up Study - Amare Wondim; Bethelihem Tigabu; Mengistu Mekonnen Kelkay (Hindawi Limited, 2020)
Background. Ethiopia is one of the countries in sub-Saharan Africa with the highest rates of severe acute malnutrition. Early recovery is a performance indicator for severe acute malnourished children for the therapeutic feeding. Despite the available interventions to tackle nutritional problems, there is scarce information on time to recovery and its determinants among children with SAM in Ethiopia. Objective. The study is aimed at assessing time to recovery from severe acute malnutrition and its predictors among admitted children aged 6-59 months at the therapeutic feeding center of Pawi General Hospital, northwest Ethiopia, from January 2013 to December 2017. Methods. An institution-based retrospective follow-up study was conducted among 398 children aged 6-59 months. The data were collected by using data extraction sheet. The data were cleaned and entered using EpiData version 4.2.0.0 and exported to Stata version 14 statistical software for further analysis. Kaplan-Meier survival curve was used to estimate median nutritional recovery time after initiation of inpatient treatment, and log-rank test was used to compare time to recovery between groups. The Cox proportional regression model was used to identify the predictors of recovery time. Adjusted hazard rate with its 95% CI was reported to show strength of relationship. Results. The recovery rate was 5.3 per 100 person-day observations, and the median recovery time was 14 days (95% CI: 13-15). The lower chance of early recovery was found among children who were not fully vaccinated (AHR: 0.73 (95% CI: 0.56, 0.96)), while high chance of recovery was found among children who had no anemia (AHR: 1.66 (95% CI: 1.23, 2.23)), TB (AHR: 2.03 (95% CI: 1.11, 3.71)), and malaria infection (AHR: 1.54 (95% CI: 1.09, 2.17)) at admission. Conclusion and Recommendation. The overall nutritional recovery rate was below the accepted minimum standard. Children not fully vaccinated and children without malaria, anemia, and TB comorbidities at admission had a higher chance of recovering early from severe acute malnutrition. Hence, treating comorbidities is vital for prompt nutritional recovery.